Inside interior spaces - Perkins+Will (ORO Editions, 2013)
This is the first in-depth book celebrating the interior spaces created by Perkins+Will. Focused on how design affects the way people live, work, learn, and heal, the book is a stunning overview of the firm's interior design portfolio. Established in 1935 and known as a leader in design innovation, sustainability, and social responsibility, Perkins+Will has grown to over 1,500 employees in 22 offices worldwide. ... This book features beautiful photography of projects from around the world, including museums, primary schools, colleges, hospitals, workspaces, libraries, and recreation centers. The images capture the way a space can create personal and meaningful moments through the way light hits a wool carpet, the texture of a reclaimed wood wall, or the way a five-story atrium takes your breath away--one can imagine the sounds, the smells, and the energy of these spaces where art and materiality intersect.